Something about Z-penguins I want to tell - Haisch, U (2008)
We stress that in models with constrained minimal flavor violation large negative corrections to the flavor-changing Z-penguin amplitudes are excluded by the precision measurements of the Z -> b anti-b pseudo observables performed at LEP and SLC. The derived stringent range for the non-standard contribution to the universal Inami-Lim function C leads to tight two-sided limits for the branching ratios of all Z-penguin dominated flavor-changing K- and B-decays.